Cahokia ancient America's great city on the Mississippi - Pauketat, Timothy R. (New York Viking, 2009)
Almost a thousand years ago, a Native American city flourished along the Mississippi River near what is now St. Louis. Cahokia was a thriving metropolis at its height, with a population of 20,000, a sprawling central plaza, and scores of spectacular earthen mounds. The city gave rise to a new culture that spread across the plains; yet by 1400 it had been abandoned, leaving only the giant mounds as monuments, and traces of its influence in tribes we know today. Here, anthropologist Timothy R. Pauketat reveals the story of the city and its people as uncovered by American archaeologists. Their excavations have revealed evidence of a powerful society, including complex celestial timepieces, the remains of feasts big enough to feed thousands, and disturbing signs of large-scale human sacrifice. Pauketat provides a comprehensive picture of what's been discovered about Cahokia, and how these findings have challenged our perceptions of Native Americans.--From publisher description.
The mother of Native North America -- Supernova -- Walking into Cahokia -- The original rolling stones -- Ghosts of archaeologists -- Discovery at Mound 72 -- Twin heroes -- American Indian royalty -- Digging for the goddess -- Wrestling with the gods -- Treasure maps of the past -- High plains drifting.
Includes bibliographical references and index.
Keywords: Mississippian culture -- Illinois -- Cahokia Mounds State Historic Park (Ill.); Excavations (Archaeology) -- Illinois -- Cahokia Mounds State Historic Park (Ill.); Cahokia Mounds State Historic Park (Ill.).; American Bottom (Ill.) -- Antiquities